(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. I gruppi etico-deontologici e il diritto della polis democratica alla luce dei recenti cambiamenti sociali vissuti dalle identità collettive - 2. I codici di autoregolamentazione nel settore del lavoro - 3. Il mercato tra codificazione etica ed eteroregolamentazione - 4. Le recenti opportunità di lavoro socialmente utile offerte dalle tecnologie social alle smart communities - 5. La nuova sensibilità deontologica nel mondo finanziario: le banche etiche e la finanza islamica - 6. La rilevanza nell’ordine della polis dei vari tipi di norme contenute nei codici deontologici: attualità e prospettive inter- e/o trans-culturali. Codes of ethics and Deontology in the fields of Labor, Market and Finance. Freedom of Conscience and the Transition from Oeconomicus Corporatism to Democratic Intercultural Cooperation ABSTRACT: The paper analyzes the recent relevance of deontological codes, from which a process of enriching the concept of deontology seems to emerge. This is increasingly understood not only in a corporatist way as an ethics of conduct within the category of reference, but also in a democratic way as the ethics of service made to the polis by professional communities, which now, in the overall world of work, appear ethically inspired in the most varied ways. Following the development that freedom of conscience has experienced in its various forms of collective exercise, we are positively experiencing new patterns of work organization where deontology represents a synthesis between moral and law. Similarly, to churches, even some professional communities have useful, non-utilitarian relationships, and open to democratic intercultural cooperation, with their multiform and typical ways of working in the service of the human person, elected to lifestyles or spiritual missions. In order to encourage and extend this phenomenon of greater ethical accountability of free professions, some legal channels will be analyzed to better harmonize the use of those new deontological standards with legal rules in order to ensure balance and order at a general level, and to avoid the social dissociation in neo-corporatist groups.